Hubungan antara Kekuatan Menggenggam dan Kecepatan Berjalan pada Lanjut Usia - Marti Rustanti; Nur Basuki (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: The aging process causes a decrease in body function, especially in the musculoskeletal system, such as reduced muscle strength, flexibility, endurance and bone density which can increase the risk of falls in the elderly. A decrease in muscle strength in the upper extremities is characterized by a decrease in gripping ability, while in the lower extremities it is characterized by a decrease in walking ability, including walking speed. Objectives: This study aims to determine the relationship between grip strength and walking speed in elderly women. Methods: This research uses an observational method with a cross sectional approach. Measurements were made on grip strength using a handgrip dynamometer measuring instrument and walking speed using a 4 meter walk test measuring instrument on elderly women who were physically healthy and did not experience functional disorders, especially the function of grasping and walking independently. The data was analyzed to determine the relationship between the two variables. Results: The results showed that there was a significant relationship between grip strength and walking speed with a p value <0.005 and a correlation coefficient r = -0.555 which showed a fairly strong relationship in the negative direction. where the decreasing grip strength increases the walking speed of the elderly. Conclusion: It was concluded that there is a fairly strong relationship between grip strength and walking speed in elderly women. Keywords: Grip Strength, Walking Speed, Elderly Women.